Validasi Pengembangan Modul Ajar Virus Berbasis Problem Based Learning (PBL) Untuk Mata Pelajaran Biologi Fase E SMA/MA - Yauma Ilban Ali; Syamsurizal Syamsurizal (Departement of Mathematics Education, 2024)
In the Merdeka Curriculum, teachers are required to develop learning tools that include Learning Outcomes (CP), Learning Objective Flow (ATP), and teaching modules as a mandatory task for teachers. The implementation of the Independent Curriculum is still faced with a number of obstacles. Teachers experience difficulties in implementing learning based on the Independent Curriculum, mainly due to a lack of adequate socialization. Teachers need time to learn to adapt to new curriculum changes. One of the demands of the Independent Curriculum is the preparation of learning tools in the form of teaching modules. However, observation results show that teachers still do not have complete teaching modules, especially for phase E. This teaching module is a learning plan in the Independent Curriculum which contains worksheets for students and teaching materials. This research uses a type of development research with a 4D model, which consists of the Define, Design, Develop and Disseminate stages. However, due to time constraints, the Disseminate stage was not carried out in this study. The research subjects included two lecturers from the Biology department, FMIPA UNP and five Biology teachers. Based on the research results, the virus teaching module developed based on problem based learning is considered very valid with a validation value of 91%, and has a readability level with very readable criteria, with a readability value reaching 94%.